2004
DOI: 10.1128/iai.72.10.6061-6067.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvumat Different Developmental Stages Modulates Host Cell Apoptosis In Vitro

Abstract: We studied apoptosis in a human ileocecal adenocarcinoma tumor cell line (HCT-8) infected with Cryptosporidium parvum, from 2 to 72 h postinfection (h.p.i.). At 2 h.p.i., the percentage of annexin V-positive cells in the cell culture had increased to 10% compared to 2.5% in noninfected control culture; sorted infected cells expressed mRNA of FasL, the active form of caspase 3, and high caspase 3 activity, whereas the noninfected neighboring cells sorted from the same culture showed no signs of apoptosis. At 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 31 publications
6
82
0
1
Order By: Relevance
“…In accordance with previous reports (14,37) The mechanisms by which FasL is translocated to the membrane and released from infected cells are unclear and currently under investigation. C. parvum activates kinase pathways in infected cells (10,11,16); we recently demonstrated that there is recruitment of transporters and channels to the site of infection (15), consistent with the active recruitment of vesicles to the plasma membrane.…”
Section: Discussionsupporting
confidence: 69%
“…In accordance with previous reports (14,37) The mechanisms by which FasL is translocated to the membrane and released from infected cells are unclear and currently under investigation. C. parvum activates kinase pathways in infected cells (10,11,16); we recently demonstrated that there is recruitment of transporters and channels to the site of infection (15), consistent with the active recruitment of vesicles to the plasma membrane.…”
Section: Discussionsupporting
confidence: 69%
“…In 6/16 animals (37.5%) (mice nos. 7,8,15,16,24, and 32), lesions were detected in more than one organ with a maximum score of histologic severity of 11 in mouse no. 16 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we showed that deep immunosuppression alone did not entail neoplasia in uninfected hosts. Taking into account that C. parvum is able to modulate apoptosis of intestinal cells during its replication, 7 a mechanism known to be involved in the carcinogenesis processes, 8 and that SCID mice developed a chronic C. parvum infection with dose-dependent pathologic effects, 9 we further studied C. parvum -induced gastrointestinal neoplasia using variable doses of C. parvum inocula and the cell proliferation marker Ki-67. The Ki-67 nuclear antigen has been shown to be expressed in proliferating cells during G 1 , S, G 2 , and mitosis stages of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) has also deemed Opisthorchis viverrini and Clonorchis sinensis infections to be carcinogenic factors in the development of biliary tract cancer (24). Those chronic parasitoses may affect apoptosis and DNA repair disturbances (25,26).…”
Section: Discussionmentioning
confidence: 99%